Menulis Ilmiah Bahasa Indonesia Berdasarkan Pendekatan Komunikatif - Sobri Sobri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2017)
The research is aimed at developing a teaching material of Indonesian scientific writing based on a communicative approach. The research method applied is the research development one, the data collection techniques used are observations, interviews, and questionnaires. The data analysis of qualitative and quantitative approaches are employed. The finding of the result is the effectiveness of class with communicative approach is 77,00 mean while, The effectiveness of class with conventional approach is 68,17. The students of activity in using of model communicative approach was higher more than 91% and the students of activity with not using of model communicative approach is 70%, it can be concluded that the implementation of communicative approach in scientific writing can improve the result of students scientific writing.